Impaired Endothelial Function and Blood Flow in Repetitive Strain Injury - Brunnekreef, J. J.; Benda, N.M. M.; Schreuder, T.H. A.; Hopman, M.T. E.; Thijssen, D.H. J. (International Journal of Sports Medicine, 2012)
Repetitive Strain Injury (RSI) is a disabling upper extremity overuse injury that may be associated with pathophysiological changes in the vasculature. In this study we investigated whether RSI is associated with endothelial dysfunction and impaired exercise-induced blood flow in the affected forearm. 10 patients with RSI (age, 40.2±10.3; BMI, 23.8±3.3) and 10 gender- and age-matched control subjects (age, 38.0±12.4; BMI, 22.7±3.4) participated in this study. Brachial artery blood flow was measured at rest and during 3-min periods of isometric handgrip exercise at 15%, 30% and 45% of the individual maximal voluntary contraction. Brachial artery endothelial function was assessed as the flow mediated dilation (FMD), by measuring brachial artery diameter and velocity before and after 5-min ischemic occlusion. We found a lower exercise-induced brachial artery blood flow in patients with RSI than in controls (p=0.04). Brachial artery FMD was significantly lower in patients with RSI than in controls (p<0.01), whilst a lower FMD was also found in patient with unilateral RSI when comparing the affected arm with the non-affected arm (p=0.04). Our results suggest that patients with RSI have an attenuated exercise-induced blood flow and an impaired endothelial function in the affected arm. These findings importantly improve our understanding of the pathophysiological mechanism of RSI.
Keywords: cumulative trauma disorder; blood vessel; endothelium; exercise; ultrasonography